1992
DOI: 10.1177/019262339202000210
|View full text |Cite
|
Sign up to set email alerts
|

Renal Lesions Induced by Ochratoxin A Exposure in the F344 Rat

Abstract: Groups of 80 male and female F344 rats were exposed by gavage to ochratoxin A, a naturally occurring mycotoxin, at levels of 21, 70, and 210 micrograms/kg body weight for up to 2 years. Ochratoxin A induced non-neoplastic renal tubular epithelial changes consisting of cytoplasmic alteration, karyomegaly, degeneration, and cysts. Exposure-related renal tubular proliferative lesions included focal hyperplasia, tubular cell adenoma, and tubular cell carcinoma. Renal tubular cell adenoma occurred as early as 9 mon… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

7
62
1

Year Published

1999
1999
2015
2015

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 116 publications
(70 citation statements)
references
References 18 publications
7
62
1
Order By: Relevance
“…Some rather small carcinomas and a few adenomas were discovered in an early stage of proliferation. Unfortunately, direct anatomical comparison of the present tumours with those in the NTP (Boorman 1989, Boorman et al 1992) and other lifetime studies is constrained by a lack of available published data. The present time course of incidence of rats with a renal carcinoma (20%) was compared with that in the NTP study by means of Cox proportional-hazard regression (see Table I, Figure 3).…”
Section: Discussionmentioning
confidence: 97%
“…Some rather small carcinomas and a few adenomas were discovered in an early stage of proliferation. Unfortunately, direct anatomical comparison of the present tumours with those in the NTP (Boorman 1989, Boorman et al 1992) and other lifetime studies is constrained by a lack of available published data. The present time course of incidence of rats with a renal carcinoma (20%) was compared with that in the NTP study by means of Cox proportional-hazard regression (see Table I, Figure 3).…”
Section: Discussionmentioning
confidence: 97%
“…The incidence of renal tubular carcinoma in male rats (60%) was the highest incidence of renal cell carcinomas found in any of the NTP studies. 5 The carcinogenic mechanism of OTA has not been elucidated, and genotoxicity results are contradictory. Castegnaro et al 8 compared OTA-induced renal carcinogenicity and DNA adducts in DA and Lewis rats of both sexes and reported that formation of these adducts appears to be correlated with toxicity and carcinogenicity.…”
Section: Discussionmentioning
confidence: 99%
“…2 Long-term animal studies have been conducted in rats and mice, and carcinogenic potential was reported in these species. [3][4][5] An NTP study in rats 6 reported that OTA induced uncommon tubular adenomas and tubular cell carcinomas of the kidney and multiple fibroadenomas of the mammary glands; on the basis of these results, the NTP classified OTA as having clear evidence of carcinogenic activity.Patients in the Balkan area who suffer from BEN have the EM profile for DB. 1 Accordingly, DA and Lewis rats were selected on the basis of their metabolic profiles as PMs and EMs, respectively, for DB in liver.…”
mentioning
confidence: 99%
“…However, most recent preliminary experiments from two independent laboratories failed to reproduce the latter data and thus failed to confirm the reported genotoxic activity of OTA (Dietrich and Turesky, personal communication). A two year mouse and rat bioassay (Bendele et al, 1985;Boorman et al, 1992), however, demonstrated that OTA is a potent renal carcinogen. These studies, revealed also a pronounced sex and species difference in kidney tumor induction, i.e.…”
Section: Introductionmentioning
confidence: 99%
“…The incidence of renal carcinomas was 28%. Female rats, on the other hand, were approximately 10-fold less responsive although not refractive to renal tumor induction (Boorman et al, 1992). Although several studies have been carried out to elucidate the mechanism(s) involved in OTA induced nephrotoxicity and carcinogenicity, little is known about the mechanism(s) leading to the observed sex and species differences.…”
Section: Introductionmentioning
confidence: 99%